2021
DOI: 10.1101/2021.12.17.472912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 synonymous codon usage evolution throughout the COVID-19 pandemic

Abstract: SARS-CoV-2, the seventh coronavirus known to infect humans, can cause severe life-threatening respiratory pathologies. To better understand SARS-CoV-2 evolution, genome-wide analyses have been made, including the general characterization of its codons usage profile. Here we present a bioinformatic analysis of the evolution of SARS-CoV-2 codon usage over time using complete genomes collected since December 2019. Our results show that SARS-CoV-2 codon usage pattern is antagonistic to, and it is getting farther a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
(135 reference statements)
2
4
0
Order By: Relevance
“…To decipher the evolutionary trend of CAI as the pandemic developed, we compared the CAI values of the SARS-CoV-2 genomes collected on different dates. Consistent with previous findings that CAI decreased during the first four ( 31 ) and 18 months ( 32 ) of SARS-CoV-2 evolution in humans, we also observed such a pattern ( Figure 1a , the red lines). However, we observed a turning point of CAI around November 26, 2021, roughly 23 months after the initiation of the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To decipher the evolutionary trend of CAI as the pandemic developed, we compared the CAI values of the SARS-CoV-2 genomes collected on different dates. Consistent with previous findings that CAI decreased during the first four ( 31 ) and 18 months ( 32 ) of SARS-CoV-2 evolution in humans, we also observed such a pattern ( Figure 1a , the red lines). However, we observed a turning point of CAI around November 26, 2021, roughly 23 months after the initiation of the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 92%
“…SARS-CoV-2, the etiology of the Coronavirus Disease 2019 (COVID- 19), has a codon usage pattern different from that of humans and bats (15,(27)(28)(29)(30). Studies have revealed that as the pandemic spread, SARS-CoV-2's codon usage pattern diverged further from that of its human hosts rather than evolving to use more optimized codons (31,32). Despite these discoveries, the evolutionary driving forces underlying the optimization and deoptimization of codons in SARS-CoV-2 are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have shown that rare codons often occur in large clusters within protein coding sequences. In the case of SARS-CoV-2, previous codon usage analyses show an antagonistic codon usage pattern (i.e., use of rare codons) reducing translation speed, but increasing its precision, and yielding accurate and correctly folded viral proteins [1]. At that end, clustering of protein sequences are investigated based on Relative Synonymous Codon Usage (RSCU) as well as edit distances of amino acid (AAc) sequences providing for both characterizing (identifying) specific protein groups (types) and temporal evolution of proteins within groups (types).…”
Section: Motivation and Aimmentioning
confidence: 99%
“…The ENC (effective number of codons) plot indicated natural selection being a driving force of codon deoptimization, especially for genes of the spike protein and the RNA-dependent RNA polymerase [74]. Mogro et al discovered a downward trend of codon adaptation index (CAI) of SARS-CoV-2 in multiple human tissues, and surprisingly, the Omicron variant (BA.1) had a higher CAI than other variants of concern, although lower than the earliest isolates [75]. Wu et al experimentally demonstrated higher protein expression when codon usage was restored to optimum, and the group also found a sudden increase in CAI when Omicron came to the scene [76].…”
Section: Accumulation Of Non-selectable Mutationsmentioning
confidence: 99%